2019
DOI: 10.1002/adfm.201901480
|View full text |Cite|
|
Sign up to set email alerts
|

All‐in‐One Phototheranostics: Single Laser Triggers NIR‐II Fluorescence/Photoacoustic Imaging Guided Photothermal/Photodynamic/Chemo Combination Therapy

Abstract: Development of single near‐infrared (NIR) laser triggered phototheranostics for multimodal imaging guided combination therapy is highly desirable but is still a big challenge. Herein, a novel small‐molecule dye DPP‐BT is designed and synthesized, which shows strong absorption in the first NIR window (NIR‐I) and fluorescence emission in the second NIR region (NIR‐II). Such a dye not only acts as a dual‐modal contrast agent for NIR‐II fluorescence and photoacoustic (PA) imaging, but also serves as a combined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
231
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 318 publications
(232 citation statements)
references
References 70 publications
1
231
0
Order By: Relevance
“…More recently, the "NIR-II" window (1000-1700 nm) has also been attracting interest because of the decreased light scattering by tissues, lower background autouorescence, and deeper tissue penetration. 95,96 Vankayala et al reported a mercaptoundecanoic acid (MUA)-protected Au NCs conjugated transactivator of transcription (TAT) peptide (peptide sequence: N-GRKKRRQRRR-C). 97 The TAT peptide-Au NCs not only produced 1 O 2 under NIR-II light (980 nm), but also acted as DNA nano-cargo to achieve high gene transfection efficiencies (z81%) in HeLa cells (Fig.…”
Section: Basic Principle Of Photosensitization For Pdtmentioning
confidence: 99%
“…More recently, the "NIR-II" window (1000-1700 nm) has also been attracting interest because of the decreased light scattering by tissues, lower background autouorescence, and deeper tissue penetration. 95,96 Vankayala et al reported a mercaptoundecanoic acid (MUA)-protected Au NCs conjugated transactivator of transcription (TAT) peptide (peptide sequence: N-GRKKRRQRRR-C). 97 The TAT peptide-Au NCs not only produced 1 O 2 under NIR-II light (980 nm), but also acted as DNA nano-cargo to achieve high gene transfection efficiencies (z81%) in HeLa cells (Fig.…”
Section: Basic Principle Of Photosensitization For Pdtmentioning
confidence: 99%
“…Nonfluorescent DCFH‐DA can be rapidly converted to green fluorescent product (2′,7′‐dichlorofluorescein, DCF) in the presence of 1 O 2 . [ 20 ] As displayed in Figure 4H, HeLa cells incubated with FA‐CNPs and DCFHDA exhibited bright green fluorescence upon 808 nm laser irradiation. But no obvious fluorescence was observed in nonirradiated controlled experiment and the case of addition of Vc in above system (Figure 4I).…”
Section: Resultsmentioning
confidence: 99%
“…To date, considerable efforts have been devoted to devise multifunctional sensitizing agents for effective single NIR‐triggered PDT and PTT combination therapy. [ 6–25 ] A number of porphyrins and phthalocyanine derivatives‐based drugs have been utilized in clinical PDT therapy. Not surprisingly, thus, many efforts are being made to develop new dual phototherapy agents based on these materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local hyperthermia can disassemble amyloid deposits by interfering with their growth . Many breakthroughs in the research and applications of photothermal agents have been reported . Nevertheless, materials currently under investigation for photothermal disintegration of matured fibrils are limited to gold and carbon‐based nanostructures.…”
Section: Introductionmentioning
confidence: 99%